Environmental effect on the occurrence of anti-Neospora caninum antibodies in pampas-deer (Ozotoceros bezoarticus) - Tiemann, JCH; Souza, SLP; Rodrigues, AAR; Duarte, JMB; Gennari, S. M. (Elsevier B.V., 2005)
Sera obtained from pampas-deer (Ozotoceros bezoarticus) captured in two different Brazilian environments were analyzed for the presence of anti-Neospora caninum antibodies by the indirect fluorescent antibody test (IFAT). Samples were collected from 23 animals from a savanna area in the National Park of Emas, in the state of Goias, Brazil. This area is surrounded by cultivated lands and allows very little contact between wild and domestic animals. Another batch of samples was collected from 16 animals from the Pantanal region, in the state of Mato Grosso, Brazil. This area is a flood plain where domestic animals have intensive contact with cervids. The 39 samples were analyzed (IFAT >= 1:50), and the values for the occurrences found in the animals from each region were compared by the test for comparison of two proportions. of the 39 cervids examined, 38.46% (15) had anti-N. caninum antibodies. Three (13%) of the 23 samples from the National Park of Emas. and 12 (75%) of the 16 samples from the Pantanal were positive, with significant differences between regions (p < 0.001). These results suggested that the presence of domestic animals, mainly dogs and cattle, may be responsible for the greater occurrence of N. caninum in the Pantanal cervids.Thus, as a recommendation of the Conservation Units that care for the pampas-deer, attention should be taken to carefully monitor the flow of diseases between the domestic animals and this species. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Neospora caninum; Ozotoceros bezoarticus; Pampas deer; Brazil; epidemiology